2017
DOI: 10.1037/emo0000256
|View full text |Cite
|
Sign up to set email alerts
|

The whole is not the sum of its parts: Specific types of positive affect influence sleep differentially.

Abstract: Given the known detrimental effects of poor sleep on an array of psychological and physical health processes, it is critical to understand the factors that protect sleep, especially during times of stress when sleep particularly suffers. Positive affect (PA) arises as a variable of interest given its known associations with health and health behaviors and its ability to buffer stress. In 2 studies, we examined which types of PA (distinguished by arousal level and trait/state measurement) were most beneficial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 118 publications
(147 reference statements)
3
34
1
Order By: Relevance
“…For example, we were not able to examine associations with low arousal momentary PA (such as states of being calm or pleased) versus high arousal PA (e.g., excited) using our momentary measures. This is important because emerging evidence suggests that low arousal PA may be uniquely important for health (Jones, Graham-Engeland, Smyth, & Lehman, 2018; Pressman, Jenkins, Kraft-Feil, Rasmussen, & Scheier, 2017; Schwerdtfeger, Friedrich-Mai, & Gerteis, 2015). Further, variation in PA related to daily stressors has been associated with peripheral inflammation (Sin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we were not able to examine associations with low arousal momentary PA (such as states of being calm or pleased) versus high arousal PA (e.g., excited) using our momentary measures. This is important because emerging evidence suggests that low arousal PA may be uniquely important for health (Jones, Graham-Engeland, Smyth, & Lehman, 2018; Pressman, Jenkins, Kraft-Feil, Rasmussen, & Scheier, 2017; Schwerdtfeger, Friedrich-Mai, & Gerteis, 2015). Further, variation in PA related to daily stressors has been associated with peripheral inflammation (Sin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Pressman et al. () found that vigour was associated with quality of sleep, whereas calmness was linked to less sleep. Hence, analysis of discrete affective states could provide more insight into the affective underpinnings between affect and health.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that, when modelled simultaneously, both positive and negative affect are associated with health (e.g. Pressman, Jenkins, Kraft‐Feil, Rasmussen, & Scheier, ), yet there is a need to investigate this relationship over longer periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…According to this view, positive affect items reflecting higher energy are in fact just markers of perceived health that are not controlled by baseline measures of physical health and fitness. For example, differences in positive energy may reflect differences in restorative behaviors such as sleep or even reflect not feeling physically well [45].…”
Section: Discussionmentioning
confidence: 99%